Mouse Models of Nonalcoholic Steatohepatitis: Toward Optimization of Their Relevance to Human Nonalcoholic Steatohepatitis. Issue 5 (12th April 2019) - Farrell, Geoff; Schattenberg, Jörn M.; Leclercq, Isabelle; Yeh, Matthew M.; Goldin, Robert; Teoh, Narci; Schuppan, Detlef
Abstract : Nonalcoholic steatohepatitis (NASH) arises from a variable interplay between environmental factors and genetic determinants that cannot be completely replicated in animals. Notwithstanding, preclinical models are needed to understand NASH pathophysiology and test mechanism‐based therapies. Among several mouse models of NASH, some exhibit the key pathophysiologic as well as histopathologic criteria for human NASH, whereas others may be useful to address specific questions. Models based on overnutrition with adipose restriction/inflammation and metabolic complications, particularly insulin resistance, may be most useful to investigate critical etiopathogenic factors. In‐depth pathologic description is required for all models. Some models demonstrate hepatocyte ballooning, which can be confused with microvesicular steatosis, whereas demonstration of an inflammatory infiltrate and pattern of liver fibrosis compatible with human NASH is desirable in models used for pharmacologic testing. When mice with specific genetic strains or mutations that cause overeating consume a diet enriched with fat, modest amounts of cholesterol, and/or simple sugars ("Western diet"), they readily develop obesity with liver disease similar to human NASH, including significant fibrosis. Purely dietary models, such as high‐fat/high‐cholesterol, Western diet, and choline‐deficient, amino acid–defined, are similarly promising. We share concern about using models without weight gain, adipose pathology, or insulin resistance/hyperinsulinemia and with inadequate documentation of liver pathology. NASH‐related fibrosis is a key endpoint in trials of possible therapies. When studied for this purpose, NASH models should be reproducible and show steatohepatitis (ideally with ballooning) and at least focal bridging fibrosis, while metabolic factors/disordered lipid partitioning should contribute to etiopathogenesis. Because murine models are increasingly used to explore pharmacologic therapies for NASH, we propose a minimum set of requirements that investigators, drug companies, and journals should consider to optimize their translational value.